The Effect of Dividend Yield, Dividend Payout Ratio, and Stock Volume on the Dividend Trap in IDXHIDIV20 - Fitria Oktaviani Putri; Indah Oktari Wijayanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
A dividend trap is a condition where investors are trapped buying shares at high prices, and the share price continues to fall after the cum date. Investors typically consider dividend yield (DY), dividend payout ratio (DPR), and stock volume as key indicators for evaluating the potential risk of a dividend trap when making investment decisions. This research seeks to examine the impact of dividend yield (DY), dividend payout ratio (DPR), and stock volume on the occurrence of the dividend trap in companies listed in IDXHIDIV20 during the 2023 period. The dividend trap is measured through stock returns taken from the day of the General Meeting of Shareholders (GMS) until the day of dividend distribution. This research’s 2023 dividend distribution schedule and financial statements serve as secondary data. Companies in IDXHIDIV20 for the period 2023 are used as the population in this study. The purposive sampling technique was used to take samples in this study. Panel data regression analysis is used as the analysis method in this study using Eviews 12. This regression tool is used to analyze dividend yield (DY), dividend payout ratio (DPR), and stock volume. Referring to the results of the analysis, it is concluded that partially DY has a negative significant effect on dividend traps, while DPR and stock volume show no significant effect. Simultaneously, DY, DPR, and stock volume have a significant effect on dividend traps.